ANALISIS KANDUNGAN FITOKIMIA DAN PROKSIMAT PADA RUMPUT LAUT COKLAT (Sargassum sp) - Kaliky, Nurainy; Atnangar, Rifaldi A (Gapenas Publisher, 2025)
The brown seaweed Sargassum sp., belonging to the class Phaeophyceae, is one of the most common brown algae found in the coastal waters of Fiditan Village, North Dullah District. This brown seaweed typically grows in clear waters with high salinity and good water circulation. It is widely utilized and favored by the local community. However, the phytochemical and proximate composition analyses of seaweed from this area have not yet been conducted. The purpose of this study was to analyze the phytochemical and proximate contents of the brown seaweed Sargassum sp. from the class Phaeophyceae. The research employed a laboratory experimental method, and data were analyzed descriptively using IBM SPSS version 23. The results showed that the brown seaweed contains alkaloids, terpenoids, steroids, phenolics, and saponins, which are known as natural antioxidants. Meanwhile, the proximate analysis revealed that the seaweed contains 8.03% carbohydrates, 73.3% moisture, 0.45% protein, and 5.09% ash content. These values meet the Indonesian National Standard (SNI) for fresh seaweed, indicating good quality.